Landscape theory. Nature in contemporary spanish narrative - Álvarez Méndez, Natalia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The paper studies the thematization of landscape in literature and its typologies, offering a state of the question and a study of the particular case of José María Merino's trilogy Los espacios naturales.
Keywords: landscape in literature; space; José María Merino; Los espacios naturales